Reconstrucción virtual de la Estancia Jesuítica de Nuestra Señora de Belén (Calera de las Huérfanas) - Marcelo Payssé Álvarez; Jacqueline Geymonat Bonino (Virtual Archaeology Review)
The present project consists of the three-dimensional recreation of the Jesuitical Farm of Bethlehem, as it was approximately in 1790, including the topography, architecture, notable buildings, territory, equipment, etc., that allow tours across animations, stereoscopic images, layouts and engravings of the epoch, by means of immersive applications.